A review on lab-on-chip as a potential diagnostic tool for early detection of Plasmodium knowlesi - Maketar, Solihah; Abu Bakar, Nurhidanatasha (Life Sciences, Medicine and Biomedicine, 2020)
Massive elimination efforts have been done to control the malaria disease caused by the emergence of the fifth human malaria parasite known as Plasmodium knowlesi. Early detection of the parasite is important in treating malaria infection. Microscopic examination of Giemsa-stained thick and thin blood films is the gold standard for laboratory malaria diagnosis, while rapid diagnostic tests (RDTs), polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) are significant diagnostic techniques to detect acute infection. However, these methods have several limitations in which it could delay the treatment. The potential of lab-on-chip (LOC) as a point-of-care diagnostic tool for malaria fulfils the requirement of limitations where it is able to produce early detection of malaria infection. This review discusses advantages and disadvantages of malaria diagnostic methods as well as new approaches that could be used for high speed, sensitive and reliable malaria detection to prevent the disease from causing severe complications and even fatal if left untreated.